A randomized trial of electronic fetal monitoring in preterm labor: mothers' views - Killien, M G; Shy, K (Birth (Berkeley, Calif.), 1989)
To determine if perceptions of preterm labor and birth differed between women who were monitored by electronic fetal monitoring (EFM) or by periodic auscultation, 135 subjects were randomly assigned to one of two treatment groups on admission to a tertiary perinatal care setting. The first group received external monitoring by continuous Doppler and tocodynamometer when membranes were intact, and with an internal fetal scalp electrode and pressure catheter once membranes were ruptured. The second group received periodic monitoring with a DeLee fetoscope or amplified Doppler. All women were cared for on a one-to-one basis by expert study nurses. Subjects completed a questionnaire about their labor experience during their postpartum hospital stay. There was no statistically significant difference between the two groups on the study measures [T2(7,81) = 13.65; F = 1.82; P greater than 0.05]. Forty-four percent of the variance in women's global evaluation of labor was explained by their perceptions of nursing support. These findings suggest that mothers' perceptions of their preterm labor are less influenced by the technologic interventions used than by the supportive care received from nurses.